Co-Designing Climate- Smart Legume Production Guides in the Southern Africa Region: Consultative Workshops in Tanzania, Malawi, and Zambia - Recha, John W.M.; Magagula, Futhi; Gitau, Angela; Johnston, Angharad; Varley, Ciara; Mashizha, Tinashe; Ndlovu, Noel; Murray, Una; McKeown, Peter; Baijukya, Frederick P.; Demissie, Teferi; Chikoye, David; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The Centre for Coordination of Agricultural Research and Development for Southern Africa (CCARDESA), in collaboration with the International Livestock Research Institute (ILRI) through the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project and the University of Galway-led Legumes for Development (LEG4DEV) project, initiated the development of Climate Smart Legume Production Guides for Tanzania, Malawi, and Zambia. The blog post, Partnership between CCARDESA, CGIAR centres and national agricultural research institutes in Tanzania, Malawi and Zambia initiates development of climate-smart legume production guides, outlines the context to these workshops and manuals.